POTENSI ANTIOKSIDAN DARI EKSTRAK KULIT BATANG Bauhinia semibifida Roxb - Haiyul Fadhli; Ainun Nurain Nurdin; Melzi Octaviani (JIIS: Jurnal Ilmiah Ibnu Sina, 2019)
Has done research about the trials of antioxidant activity the extract of bark of butterfly trees (Bauhinia semibifida Roxb) with the DPPH method. Testing of antioxidant activity using n-hexane, ethyl acetate and methanol extract from the bark of the butterfly tree and Vitamin C was used as a control. Testing based on absorbance value of extract against DPPH at a wavelength of 517 nm using a microplate reader. The results showed that the IC50 value of n-hexane extract of butterfly bark was 137 µg/mL with an AAI value of 0.5 and categorized as weak, the IC50 value of ethyl acetate extract was 30.15 µg/mL with an AAI value of 1.32 and categorized as strong, and IC50 value of the methanol extract was 16 µg/mL with a an AAI value of 2.5 and categorized very strong. It shows that the methanol extract of bark of butterfly tree have a very strong antioxidant activity compared with other extracts.